AND YET ONE MORE ADDS TO THE SORROW - Haroon, Muhammad Zeeshan; Wazir, Mohammad Salim (Journal of Ayub Medical College Abbottabad, 2016)
Chikungunya is one of the vector borne diseases. It is caused by Chikungunya virus, an alpha virus, spread by the bite of female Aedes mosquito. Chikungunya is a non-fatal, self-limiting Dengue like illness which is characterized by high grade fever, headache, skin rash, and prolong debilitating arthralgia mostly affecting peripheral small joints. Treatment is usually supportive for the symptoms which includes antipyretic, analgesics and anti-inflammatory drugs. Current outbreak in Karachi is the first declared outbreak in Pakistan. To control the current outbreak, integrated vector management approach must be used to control Aedes not only to combat the current outbreak but also to reduce the endemicity and to prevent introduction of other Aedes borne diseases. Keywords: Chikungunya, Vector Borne Disease, Aedes, Alpha virus